Etnomathematics: Batik Activities In Tancep Batik - Heru Wahyudi; Sri Adi Widodo; Dafid Slamet Setiana; Muhammad Irfan (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
This study aims to examine the ethnomathematics of batik activity in the Batik Tancep Gunungkidul artwork as contextual mathematics learning. This research is a type of qualitative research with an ethnographic approach. The data was obtained in the form of qualitative data, research data sources obtained through observation, interviews, documentation. The instrument in this study was the researcher himself. Data collection is done by participant observation, in-depth interviews, and documentation. The validity of the data is done by triangulation of data collection techniques and then analyzed descriptively qualitatively. Data analysis is reduced based on Bishop's mathematical fundamental activities. The results of data analysis are then explored in mathematical aspects. The results of the study found mathematical aspects of the area of flat wake area, congruence and congruence of flat wake, comparison, translation, multiplication of count numbers, and volume of curved side space. The results of the study show that the batik activity in the Batik Tancep Gunungkidul artwork is one of the real events that can be raised into contextual mathematics learning. Keywords: Ethnomatematics, Tancep Batik, Contextual Mathematics Learning